Fetal Magnetic Resonance Imaging Detection of Liver Iron Deposition in Neonatal Hemochromatosis During Prenatal Therapy. Issue 5 (November 2016) - Sasaki, Aiko; Motomura, Kenichiro; Suyama, Fumiwo; Nagasawa, Junko; Hisano, Michi; Ito, Reiko; Miyazaki, Osamu; Nakazawa, Atsuko; Ito, Yushi; Kasahara, Mureo; Asai, Akihiro; Matsumoto, Kenji; et al.
Abstract : Supplemental Digital Content is available in the text